Development of Assignment-Based Teaching Materials And Local Wisdom For English Learning of Iisbud Sarea Students During the Pandemic - Samsudin Samsudin; Sukarismanti Sukarismanti (Universitas Pahlawan Tuanku Tambusai, 2021)
The purpose of this research is to develop assignment-based teaching materials and local wisdom for the English language learning of Iisbud Sarea students during the pandemic. Then, this research method uses the ADDIE namely development, analysis, design, development, implementation, and evaluation. The results showed that the validation test results of material expert, language expert, and media expert against the modules developed were in the